Handbook of mathematical cognition - Campbell, Jamie I. D. (Psychology Press, 2005)
How does the mind represent numbers and make mathematical calculations? What underlies the cognitive development of numerical and mathematical abilities? What factors affect the learning of numerical concepts and procedures? What are the biological bases of number knowledge? Do humans and other animals share similar numerical representations and processes? What underlies numerical and mathematical disabilities and disorders, and what is the prognosis for rehabilitation? These questions are the domain of mathematical cognition, the field of research concerned with the cognitive and neurological processes that underlie numerical and mathematical abilities. Mathematical cognition research intersects a wide array of disciplines including cognitive development, neurological development, computational science, cognitive and educational psychology, animal cognition, cognitive and clinical neuropsychology, neuroscience, and cognitive science. This collection of twenty-seven chapters by leading researchers in the field constitutes a comprehensive review of important facets of mathematical cognition. The volume thereby provides a state-of-the-art general reference for mathematical cognition research, and is intended for academics, scientists, clinicians, and senior students who want a definitive, comprehensive survey of the field.